2009
DOI: 10.1111/j.1399-3046.2007.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset post‐transplantation food allergy in children – Is it attributable only to the immunosuppressive protocol?

Abstract: New-onset post-transplantation food allergy has been described mainly after liver transplantation, and its pathogenesis was attributed to the immunomodulatory effects of tacrolimus therapy. The aim of the present study was to evaluate the association of food allergy with solid organ transplantation in our center. The medical records of children who underwent kidney transplantation and children who underwent liver or liver and kidney transplantation from 1986 to 2005 were reviewed. A total of 189 children (124 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…4,5 Our study demonstrated the same prevalence as the several worldwide reports of FA after LT which range from 6% to 57%. 9 The prevalence rate of de novo FA in this study was high compared to other reports, possibly due to the selective criteria of FA that we included all types of food allergic reactions; IgE-, non IgE-, and mixed types.…”
Section: Outgrowing Of Food Allergymentioning
confidence: 68%
See 4 more Smart Citations
“…4,5 Our study demonstrated the same prevalence as the several worldwide reports of FA after LT which range from 6% to 57%. 9 The prevalence rate of de novo FA in this study was high compared to other reports, possibly due to the selective criteria of FA that we included all types of food allergic reactions; IgE-, non IgE-, and mixed types.…”
Section: Outgrowing Of Food Allergymentioning
confidence: 68%
“…6,[8][9][10][11] While the incidence of this condition was increasing, several risk factors such as tacrolimus use, EBV viremia and younger age at transplantation have been reported but these remain inconclusive. 8,9,12,13 Furthermore, the natural history is also unclear leading to the reluctance of health care providers and child caregivers for dietary management. Therefore, this study aimed to 1) determine the prevalence of de novo FA, 2) identify risk factors of de novo FA, and 3) demonstrate the natural history of de novo FA in post LT children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations